Dietary protein-to-carbohydrate ratio and added sugar as determinants of excessive gestational weight gain: a prospective cohort study. Issue 2 (10th February 2015) - Maslova, Ekaterina; Halldorsson, Thorhallur I; Astrup, Arne; Olsen, Sjurdur F
Abstract : Objective: To examine the relation between the protein:carbohydrate (P/C) ratio and added sugar intake in pregnancy and gestational weight gain (GWG). Design: A prebirth cohort including 103 119 pregnancies enrolled between 1996 and 2003. Setting: All women in Denmark were eligible to participate if they spoke Danish and were planning to carry to term.The pregnant women were recruited and enrolled during their first antenatal visit (6–10 weeks of gestation). Participants: Participants included women with live-born singletons and complete data on dietary intake and GWG, leaving 46 262 women for the analysis. Exposure: Macronutrient intake was quantified using a validated food frequency questionnaire administered in the 25th week of gestation. The P/C ratio and added sugar intake were examined in quintiles. Primary outcome measures: GWG was based on self-reported weight in gestational weeks 12 and 30 and defined as gain in g/week. We used multivariable linear regression, including adjusting for pre-pregnancy body mass index, to calculate relative change in GWG and 95% CI. Results: Average GWG was 471(224) g/week. The adjusted weight gain was 16 g/week lower (95% CI 9 to 22, p for trend <0.001) in the highest (Q5) versus lowest (Q1) quintile of the P/C ratio (∼3% average reduction across the entire pregnancy). Weight gain for those with >20%E vs <12%E from protein was 36 g/week lower (95% CI 20 to 53, p for trend <0.0001; ∼8% average reduction). A high P/C ratio was inversely related to intake of added sugars. Added sugar consumption was strongly associated with GWG (Q5 vs Q1: 34, 95% CI 28 to 40 g/week, p for trend <0.0001). Conclusions: A high P/C ratio was associated with reduced GWG. This association appeared to be partly driven by a decrease in intake of added sugar. These results are consistent with randomised trials in non-pregnant participants. A dietary intervention targeting an increased P/C ratio with emphasis on reducing added sugar can contribute to reducing excessive GWG.